2019
DOI: 10.1039/c8ja00281a
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterisation of new glycine certified reference materials for SI-traceable13C/12C isotope amount ratio measurements

Abstract: Variations in the stable isotopic composition of carbon are used in diverse fields, including biology, environmental sciences, food and drug authentication and forensic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 32 publications
8
36
0
Order By: Relevance
“…The R sp ( 12 C/ 13 C) value was determined as the reciprocal of the R sp ( 13 C/ 12 C) value which could be measured by offline FIA-CO-IRMS analysis using previously characterised 13 C-labelled glycine with R glycine ( 13 C/ 12 C) = (211 ± 4) (expanded uncertainty, k = 2) for one point calibration [24]. Each analytical run consisted of alternate injections of the two 13 C-labelled compounds (five injections of the glycine and four of the spike).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The R sp ( 12 C/ 13 C) value was determined as the reciprocal of the R sp ( 13 C/ 12 C) value which could be measured by offline FIA-CO-IRMS analysis using previously characterised 13 C-labelled glycine with R glycine ( 13 C/ 12 C) = (211 ± 4) (expanded uncertainty, k = 2) for one point calibration [24]. Each analytical run consisted of alternate injections of the two 13 C-labelled compounds (five injections of the glycine and four of the spike).…”
Section: Resultsmentioning
confidence: 99%
“…The sample valine was analysed by FIA-CO-IRMS against synthetic isotope mixtures of glycine previously prepared for absolute carbon isotope ratio measurements. The R glycine ( 13 C/ 12 C) values of the synthetic isotope mixtures were (0.010543 ± 0.000024), (0.011070 ± 0.000025) and (0.011546 ± 0.000026) (expanded uncertainties, k = 2 [24]). Raw instrumental data were the mean and standard deviation of the integrated ion current ratios for the working gas ( n = 6 per analysis) and sample gas ( n = 5 per analysis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to the works of Santamaria-Fernandez, 64,65 Dunn 20,21 and Malinovsky, 19,22 it could be benecial to test our approach using atomic spectrometry methods, like inductively coupled plasma mass spectrometry (ICP-MS). In these studies the ion intensity ratio 13 C + / 12 C + were measured directly.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several laboratories have tried to redetermine the absolute carbon isotope ratio R 13/12 of VPDB. [14][15][16][17][18][19][20][21][22] Malinovsky et al 22 gave an overview of reported values. Currently, the recommended value of R 13/12,VPDB (ref.…”
Section: Introductionmentioning
confidence: 99%